FUNGSI DAN TANTANGAN PARTAI POLITIK DALAM MEWUJUDKAN PEMILU YANG DEMOKRATIS DAN INKLUSIF - Albert Yansen (CV. Adiba Aisha Amira, 2025)
This study aims to analyse the functions and challenges of political parties in realising democratic and inclusive elections in Indonesia through a literature review method. Political parties play a strategic role as a means of political education, cadre recruitment, channelling public aspirations, and monitoring the electoral process, all of which aim to ensure equal political participation without discrimination. However, in practice, political parties still face various obstacles, such as weak internal democracy, elite domination, money politics, low transparency and accountability, and minimal representation of vulnerable groups such as women, people with disabilities, and other minorities. Additionally, external challenges such as regulatory complexity, political fragmentation, and low-quality political education further exacerbate the situation, making the electoral process not yet fully democratic and inclusive. Therefore, internal party reforms, the implementation of affirmative policies, increased transparency, and the strengthening of inclusive political education are needed so that political parties can optimally perform their functions as the main pillars of democracy and realise truly democratic and inclusive elections in the future.